POSTHUMAN AS A PHILOSOPHICAL PROJECT: ANTHROPOLOGY OF TRANSHUMANISM IN THE CONTEXT OF POSTMODERNITY - Mohigul Nasrullaeva (Modern American Journals, 2025)
This article explores the anthropological foundations of transhumanism through the lens of postmodern philosophy. It focuses on the critical rethinking of human nature in the age of convergent technologies and highlights the posthuman as a hybrid construct emerging at the intersection of biotechnological advancement and philosophical deconstruction. Drawing on the ideas of Rosi Braidotti, N. Katherine Hayles, and Jean-François Lyotard, the study analyzes the shift from essentialist views of human identity to flexible and technologized models of subjectivity. Special attention is paid to the ethical and socio-cultural risks associated with morphological freedom, cognitive enhancement, and the erosion of traditional notions of dignity and autonomy. The article employs a comparative analysis of poststructuralist and transhumanist discourses to reveal the contradictions and potentials of the posthuman project.
Keywords: Posthumanism, transhumanism, postmodernism, philosophical anthropology, morphological freedom, identity, ethics of technology, deconstruction, convergent technologies, subjectivity.